2020
DOI: 10.3855/jidc.12779
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevention and control situation in public hospitals of Islamabad

Abstract: Introduction: Healthcare-associated infections represent a global public health challenge and are associated with significant mortality and morbidity. Infection Prevention and Control (IPC) is a neglected area in healthcare facilities across Pakistan. The objective of our study was to elucidate the current state of infection prevention and control practices in public sector hospitals of Islamabad to underscore potential areas for improvement. Methodology: A cross-sectional survey was conducted between No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 18 publications
6
34
0
1
Order By: Relevance
“…14,15 In Pakistan, the total IPCAF scores among five hospitals in Islamabad scored as inadequate. 23 In our study, HAI surveillance and monitoring and feedback of IPC practices scored lowest among low-income countries, similar to the study in Pakistan and another study in Georgia among 41 hospitals using an adapted version of the IPCAF. 23,25 Core components related to workload, staffing, and bed occupancy and IPC education and training scored the lowest across all income and care levels, irrespective of the fact that evidence supporting the WHO guidelines Only includes complete survey responses from health-care facilities that responded to both surveys overall and for the relevant core components.…”
Section: Income Levelsupporting
confidence: 87%
See 1 more Smart Citation
“…14,15 In Pakistan, the total IPCAF scores among five hospitals in Islamabad scored as inadequate. 23 In our study, HAI surveillance and monitoring and feedback of IPC practices scored lowest among low-income countries, similar to the study in Pakistan and another study in Georgia among 41 hospitals using an adapted version of the IPCAF. 23,25 Core components related to workload, staffing, and bed occupancy and IPC education and training scored the lowest across all income and care levels, irrespective of the fact that evidence supporting the WHO guidelines Only includes complete survey responses from health-care facilities that responded to both surveys overall and for the relevant core components.…”
Section: Income Levelsupporting
confidence: 87%
“…26 Gaps in the effective implementation of IPC training programmes have also been highlighted by other single-country IPCAF surveys. 23,25 In our study, very few facilities in low-income countries had access to a full-time IPC professional and significantly lower scores were found for core components 1 and 2, indicating defective IPC programmes and limited availability of guidelines. Efforts to build or participate in recognised IPC certification pathways should be strongly encouraged, such as the training programmes offered by the European Committee on Infection Control and the Infection Control African Network.…”
Section: Income Levelmentioning
confidence: 50%
“…Participants however felt it would be more useful to distribute hard copies. A few participants (12) were unsatisfied with the length of training whereas 25 remained "neutral". Analysis of open ended questions revealed that participants felt trainings were intense and should have been spread over a longer period.…”
Section: This Paper Appraises Infection Prevention and Control Training Workhops Using Level 1 And 2 Ofmentioning
confidence: 99%
“…Infection prevention and control (IPC) is a largely overlooked domain in healthcare facilities in the country. To assess the existent state of IPC in HCFs, audits were conducted using the WHO's Infection Prevention and Control Assessment Framework (IPCAF) (Savul et al, 2020). All HCFs scored poorly denoting major deficiencies in IPC implementation with need of urgent reforms (Savul et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation